Correlation of dental caries and dermatoglyphics in pediatric cases - Prakruti H Sanghani; Harleen Kaur Soni; Manjiri U Joshi (Wolters Kluwer Medknow Publications, 2016)
Background: Dental caries is a multifactorial disease, and its etiology has been advocated to various environmental and genetic factors. Dermatoglyphics is the study of dermal ridges on the palmar and plantar surfaces of hands and feet. It is genetic in nature and is unique to each individual. Enamel as well as finger buds are ectodermal in origin and develop during the same time of intrauterine life; therefore, factors affecting dental caries may cause peculiarities in dermal ridge patterns. Aim: To find a correlation between dermatoglyphic pattern and dental caries in pediatric cases. Materials and Methods: A cross-sectional study was performed on 200 children (100 caries-active and 100 caries-free) between the age range of 6-13 years. The decayed, missing, and filled teeth (DMFT) score was recorded for caries-active children having a score range of 3-6 and under each score there were 25 cases. Midlo and Cummins method (1943) of recording palm prints was used using Indiana Ink (stamp pad), roller and printing papers. The prints were inspected with the help of magnifying lens and whorls and loops in each hand were recorded. Statistical Analysis: Statistical analysis was performed using SPSS software 14.00, and Chi-square test was used for statistical analysis of collected data. Results: The number of whorls was found to be more in caries-active children with increased number of whorls in children with a higher DMFT whereas the number of loops was more in caries-free children. There was a statistically significant difference between the groups (P < 0.05). The number of whorls and loops was found to be more on the right hand as compared to the left hand. Conclusion: The results of the study indicate that there is a definite correlation between the number of whorls and loops and the presence of dental caries in children. Hence, dermatoglyphics can be used as a screening method to provide adequate preventive treatment to children showing a higher caries risk as detected by the hand ridge patterns.